A Systems Engineering Approach for Artificial Intelligence: Inspired by the VLSI Revolution of Mead & Conway. Issue 1 (15th April 2020) - Wade, Jon; Buenfil, Jorge; Collopy, Paul
ABSTRACT: Artificial intelligence is at a tipping point where the technical capabilities it enables are outstripping systems engineers' ability to employ it in viable systems. This paper reviews the very large scale integration (VLSI) revolution enabled by Mead and Conway in the late 1970's and the lessons learned from this experience. It applies these principles to engineering artificial intelligence (AI) centric systems and formulates approaches to systems engineering and education to successfully meet this critical challenge.